Nazismens kamp mod forfaldskunsten - Bolt, Mikkel (K&K - Kultur og Klasse, 2008)
Nazism’s Fight against the Art of Decay: The article presents a reading of the exhibition »Entartete Kunst« that took place in Munich in 1937. The exhibition was staged by the Nazi regime as an attempt to prove the dangerous nature of modern art. According to Nazi ideology, modern art was not just a reflection of unhealthy interests or degenerate racial mixings but was in itself a threat to the purity of the soul of the German people. Therefore modern art had to be excluded in order to make room for the appearance of the German people and its eternal art. Contrary to the idea of Nazism as being somehow not modern, the article stresses the modernist aspects of the Nazi ideology through a detailed account of Nazism’s racist ideology.